STRATEGI PEMASARAN SYARIAH DALAM MENINGKATKAN LOYALITAS PELANGGAN DI PERBANKAN SYARIAH - Merlyn Anggraini; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
This study analyzes the sharia marketing strategies employed by Islamic banks to enhance customer loyalty. Utilizing a qualitative approach, the research investigates various strategies that prioritize service quality and customer relationships, drawing on data from relevant books and journals. The findings reveal that high-quality service, customer relationship management (CRM), and sharia-compliant product innovation are essential factors in fostering customer loyalty. Adherence to sharia principles, personalized services, and continuous education regarding sharia products significantly contribute to building customer trust. Additionally, the adoption of digital technologies, such as online banking applications, has proven effective in improving accessibility and customer satisfaction. Despite challenges, including limited application socialization and uneven internet access, this study concludes that effective sharia marketing strategies can strengthen customer relationships and expand the market share of Islamic banks within the banking sector.